Методика оцінювання якості гомогенізації молочної емульсії - Самойчук, Кирило Олегович; Samoichuk, Kyryl (Мелітополь : 2022, 2022)
UA: При дослідженні змін дисперсних характеристик мікроемульсій під час обробки в диспергаторах, емульсаторах та гомогенізаторах використовують непрямі методи, які призводять до появи суттєвих похибок. Здійснено короткий аналіз основних методів визначення дисперсних характеристик мікроемульсій. Найбільш перспективним визначено метод прямого вимірювання жирових кульок в оптичному мікроскопі. Для визначення дисперсних характеристик молочних (або інших мікроемульсій) необхідні: оптичний мікроскоп з вбудованою цифровою камерою і комп’ютер. Розроблена методика визначення основних дисперсних характеристик мікроемульсій (середній діаметр, середньоквадратичне відхилення розмірів, коефіцієнт варіації з побудовою гістограм розподілу), придатну до застосування при оцінюванні якості гомогенізації молока. EN: In the study of changes in the dispersed characteristics of microemulsions during processing in dispersants, emulsifiers and homogenizers use indirect methods that lead to significant errors. A solution to the problem could be the development of a state standard for determining the quality of homogenization of milk, which does not currently exist. A brief analysis of the main methods for determining the dispersed characteristics of microemulsions: electrical (conductometric, dielectric), optical (microscopic, electron microscopic, television, ultramicroscopic, diffraction, nephelometric, scattered light), acoustic, sedimentary. The most promising method is the direct measurement of fat globules in an optical microscope. A digital camera with a device for connection to the microscope eyepiece (or instead) is used to create microphotographs of fat globules. Digital data (field of view of the microscope with emulsion samples) is transmitted to a computer, where it is stored and can be conveniently processed (already after research) using software (including free versions of computer programs). Thus, to determine the dispersed characteristics of milk (or other microemulsions) you need: an optical microscope with a built-in digital camera (or a separate digital camera that can be mounted on the eyepiece of the microscope) and a computer. A method for determining the main dispersed characteristics of microemulsions (mean diameter, standard deviation of dimensions, coefficient of variation with the construction of distribution histograms), developed for use in assessing the quality of homogenization of milk. This technique is simple, reliable and sufficiently accurate direct method of measuring the dispersed characteristics of microemulsions and is suitable for use in small research centers, educational institutions and in production conditions (dairy plants).
Method of evaluation of quality of homogenization of milk emulsion
Cамойчук К. О. Методика оцінювання якості гомогенізації молочної емульсії. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 1. C. 136-142.
Keywords: молочна емульсія; молоко; дисперсність; жирова кулька; діаметр жирової кульки; методика; milk emulsion; milk; dispersion; fat ball; fat globule; diameter; method